A Comparison of the Effect of Total Intravenous Anaesthesia with Propofol and Remifentanil and Inhalational Anaesthesia with Isoflurane on the Release of Pro- and Anti-Inflammatory Cytokines in Patients Undergoing Open Cholecystectomy - Ke, J. J.; Zhan, J.; Feng, X. B.; Wu, Y.; Rao, Y.; Wang, Y. L. (Anaesthesia and intensive care, 2008)
The aim of the study was to investigate the effects of two anaesthetic techniques (total intravenous technique vs. inhalational technique) on changes in pro- and anti-inflammatory cytokine levels during open cholecystectomy. Forty ASA PS I-II patients undergoing open cholecystectomy were randomly assigned to two groups. Group R received total intravenous anaesthesia with propofol and remifentanil and group F received balanced inhalational anaesthesia with isoflurane. The plasma levels of tumour necrosis factor-α (TNF-α), interleukin IL-6 and interleukin IL-10 were measured during and after surgery. The proinflammatory cytokine levels (TNF-α and IL-6) and the anti-inflammatory cytokine (IL-10) showed a significant increase in their concentrations compared with pre-induction levels in both groups (P <0.05). By the end of anaesthesia and surgery, TNF-α and IL-6 were significantly lower in group R than in group F (P <0.05). At the end of anaesthesia and 12 hours postoperatively, IL-10 levels in group R were higher than in group F (P <0.05). These findings suggest that total intravenous anaesthesia using propofol and remifentanil suppresses the inflammatory response caused by surgery to a greater extent than a balanced inhalation technique using isoflurane.